Application of exergoeconomic, exergoenvironmental, and advanced exergy analyses to Carbon Black production. (15th October 2017) - Mergenthaler, Pieter; Schinkel, Arndt-Peter; Tsatsaronis, George
Abstract: Carbon Black is an industrial produced material of fine carbon particles. These particles are aggregates of primary particles having a mean diameter usually below 1 μ m . Carbon Black is mainly used in printing and coating applications as a pigment, in plastic applications as a UV protector, and in rubber applications as filler material to improve mainly the mechanical properties of the rubber like stiffness and abrasion resistance. Volume wise the most important production technique is the furnace black production. For this work, a Carbon Black Plant is modeled using a free available tool called COFE. The behavior of the components was verified by measurements. The effects of components' exergy destruction on the system's exergoeconomic and exergoenvironmental behavior are analyzed. Furthermore, the interdependencies between components are studied. The burners have the highest exergy destruction among all components of the total plant. These burners however, neither have the highest impact on cost generation caused by exergy destruction, nor the highest impact on the exergoenvironmental values. Nonetheless, they contribute significantly to the exogenous exergy destruction within other components. The largest cost generation takes place within the boilers' heat exchangers. The most important components for the exergoenvironmental analysis are the reactors. Highlights: The burners have the highest exergy destruction among all components of the total plant. The largest cost generation takes place within the boilers' heat exchangers. The most important components for the exergoenvironmental analysis are the reactors.